Enhancing stress resilience in rice (Oryza sativa L.) through profiling early-stage morpho-physiological and molecular responses to multiple abiotic stress tolerance - Kumar, Kathiresan Pravin; Pushpam, Ramamoorthy; Manonmani, Swaminathan; Raveendran, Muthurajan; Santhiya, Subramanian; Senthil, Alagarsamy (Frontiers in Plant Science, 2024)
Under changing climatic conditions, crop plants are more adversely affected by a combination of various abiotic stresses than by a single abiotic stress. Therefore, it is essential to identify potential donors to multiple abiotic stresses for developing climate-resilient crop varieties. Hence, the present study was undertaken with 41 germplasm accessions comprising native landraces of Tamil Nadu, Prerelease lines and cultivars were screened independently for drought, salinity, and submergence at the seedling stage during Kharif and Rabi 2022–2023. Stress was imposed separately for these three abiotic stresses on 21-day-old seedlings and was maintained for 10 days. The studied genotypes showed a significant reduction in plant biomass (PB), Relative Growth Index (RGI), relative water content (RWC), leaf photosynthesis, chlorophyll fluorescence, and Chlorophyll Concentration Index (CCI) under drought followed by salinity and submergence. Stress-tolerant indices for drought, salinity, and submergence revealed significant variation for plant biomass. Furthermore, a set of 30 SSR markers linked to drought, salinity, and submergence QTLs has been used to characterize 41 rice germplasm accessions. Our analysis suggests a significantly high polymorphism, with 28 polymorphic markers having a 93.40% in 76 loci. The mean values of polymorphic information content (PIC), heterozygosity index (HI), marker index (MI), and resolving power (RP) were 0.369, 0.433, 1.140, and 2.877, respectively. Jaccard clustering grouped all the genotypes into two major and six subclusters. According to STRUCTURE analysis, all genotypes were grouped into two major clusters, which are concurrent with a very broad genetic base (K = 2). Statistically significant marker-trait associations for biomass were observed for five polymorphic markers, viz., RM211, RM212 (drought), RM10694 (salinity), RM219, and RM21 (submergence). Similarly, significant markers for relative shoot length were observed for RM551 (drought), RM10694 (salinity), and ART5 (submergence). Notably, the genotypes Mattaikar, Varigarudan samba, Arupatham samba, and APD19002 were identified as potential donors for multiple abiotic stress tolerance. Thus, identifying the genetic potential of germplasm could be useful for enhancing stress resilience in rice.